Effects of Macro Uncertainty on Mean Expectation and Subjective Uncertainty: Evidence from Households and Professional Forecasters - Giulia Piccillo; Poramapa Poonpakdee (Center for Economic Studies and ifo Institute (CESifo), 2021)
Macroeconomic uncertainty affects the subjective distribution of individual expectations. Using four panel datasets, we document the effects of macro uncertainty on the mean expectation (first moment) and subjective uncertainty (second moment) of income forecasts. We find that macro uncertainty reduces the mean expectation of income when using professional forecasters' data as most macroeconomic models assume. However, macro uncertainty does not have a monotonic effect on subjective uncertainty. This finding is at odds with most models, which assume higher individual subjective uncertainty as the microfoundation for the impact of uncertainty on decision-making.
Keywords: D80; D90; E70; 330; macroeconomic uncertainty; subjective uncertainty